2005
DOI: 10.1093/eurheartj/ehi430
|View full text |Cite
|
Sign up to set email alerts
|

Vascular surgery patients: perioperative and long-term risk according to the ACC/AHA guidelines, the additive role of post-operative troponin elevation

Abstract: After pre-operative stratification, patients undergoing elective major vascular surgery remain at high risk of MI and death. Events occur mainly early after surgery. cTnI elevations are frequent and independently associated with increased risk. These findings suggest the need for a major re-evaluation of our approach to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 36 publications
2
60
1
3
Order By: Relevance
“…Most of the studies that have investigated the role of perioperative measurement of cTns evaluated patients undergoing noncardiac surgery, rather than solely on TJA, and were assessing for myocardial injury [23,26,28] and infarction [21][22][23][24][25][26][27] (see Table 1). These studies have a great deal of heterogeneity in the specific assays and timing of troponin measurement, as well as specific populations within the larger grouping of noncardiac surgery.…”
Section: Troponins As a Marker Of Cardiovascular Risk In Noncardiac Smentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies that have investigated the role of perioperative measurement of cTns evaluated patients undergoing noncardiac surgery, rather than solely on TJA, and were assessing for myocardial injury [23,26,28] and infarction [21][22][23][24][25][26][27] (see Table 1). These studies have a great deal of heterogeneity in the specific assays and timing of troponin measurement, as well as specific populations within the larger grouping of noncardiac surgery.…”
Section: Troponins As a Marker Of Cardiovascular Risk In Noncardiac Smentioning
confidence: 99%
“…Thus, this review focuses on several of the larger and more applicable studies. However, overall, several studies have shown that elevated cTn levels predicted or were associated with 30-day mortality [23,27,[29][30][31] and long-term (up to 5 years) morbidity [32] or mortality [21,24,[33][34]. These studies share similarities in their limitations, strengths and weaknesses, and the majority of such findings are grouped under the 'Limitations and challenges' section unless as discussed below.…”
Section: Troponins As a Marker Of Cardiovascular Risk In Noncardiac Smentioning
confidence: 99%
See 2 more Smart Citations
“…Several potential mechanisms have been recognized to contribute to the pathophysiology of peri-operative AMI, resulting in type 1 or type 2 AMI, or due to stent thrombosis, which is particularly associated with oral anti-platelet therapy interruption [66]. Notably, the pre-operative risk assessment is of great clinical relevance, and over the past decade, cTn elevation has been recognized as a relevant prognostic factor for adverse short-and longer-term outcomes [67]. With the introduction of hsTn, the prognostic value of the marker in these patients has potentially increased according to the capability to detect very minor myocardiocyte damage.…”
Section: This Is Not the End: Other Pieces To The Puzzlementioning
confidence: 99%